2012
DOI: 10.1007/s10577-012-9309-9
|View full text |Cite
|
Sign up to set email alerts
|

The radial nuclear positioning of genes correlates with features of megabase-sized chromatin domains

Abstract: A nonrandom radial nuclear organization of genes has been well documented. This study provides further evidence that radial positioning depends on features of corresponding ∼1 Mbp chromatin domains (CDs), which represent the basic units of higher-order chromatin organization. We performed a quantitative three-dimensional analysis of the radial nuclear organization of three genes located on chromosome 1 in a DG75 Burkitt lymphoma-derived cell line. Quantitative real-time polymerase chain reaction revealed simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 90 publications
0
29
0
Order By: Relevance
“…Although they are usually represented as large chromatin globules (for review, see Mirny 2011;Fudenberg and Mirny 2012;Bickmore 2013;de Graaf and van Steensel 2013;Dekker et al 2013;Gibcus and Dekker 2013), direct experimental evidence for the existence of such globules in individual cells is controversial. Using confocal and 3D-SIM microscopy, Cremer and colleagues observed ∼1-Mb globular domains within chromosomal territories (Cremer and Cremer 2001;Kolbl et al 2012;Smeets et al 2014). However, using STORM microscopy, Ricci et al found that chromatin in individual mammalian cells is organized into "clutches" composed of several nucleosomes, and that increased histone acetylation dramatically reduces the size of these clutches (Ricci et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although they are usually represented as large chromatin globules (for review, see Mirny 2011;Fudenberg and Mirny 2012;Bickmore 2013;de Graaf and van Steensel 2013;Dekker et al 2013;Gibcus and Dekker 2013), direct experimental evidence for the existence of such globules in individual cells is controversial. Using confocal and 3D-SIM microscopy, Cremer and colleagues observed ∼1-Mb globular domains within chromosomal territories (Cremer and Cremer 2001;Kolbl et al 2012;Smeets et al 2014). However, using STORM microscopy, Ricci et al found that chromatin in individual mammalian cells is organized into "clutches" composed of several nucleosomes, and that increased histone acetylation dramatically reduces the size of these clutches (Ricci et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Across multiple species and cell types, lamin-associated domains, as revealed by DamID (DNA adenine methyltransferase identification), show low gene densities and transcriptional activity (Kind et al, 2013). Similarly, across multiple species and cell types, the radial positioning of gene loci within a cell population stochastically closer to the nucleus center is associated with higher transcriptional activity (Kölbl et al, 2012; Takizawa et al, 2008). This stochastic correlation between gene expression and radial positioning may mask a more deterministic relationship between gene expression and gene positioning relative to a specific nuclear body which itself is radially distributed.…”
Section: Introductionmentioning
confidence: 99%
“…Across multiple species and cell types, lamin-associated domains (LADs), 23 as revealed by DamID, show low gene densities and transcriptional activity (Kind et al, 2013). 24 Similarly, across multiple species and cell types, the radial positioning of gene loci within a cell 25 population stochastically closer to the center of the nucleus is associated with higher 26 transcriptional activity (Kolbl et al, 2012;Takizawa et al, 2008). This stochastic correlation 27 between gene expression and radial positioning may mask a more deterministic relationship 28 between gene expression and gene positioning relative to a specific nuclear body which itself is 29 radially distributed.…”
Section: Introductionmentioning
confidence: 99%